Report on underlying drivers of deforestation in Colombia - Vanegas, Martha; Sylvester, Janelle; Pérez Marulanda, Lisset; Marulanda, Jose (2023)
In the frame of AgriLAC resiliente, a framework to integrate climate change mitigation priorities (through low emission food systems) and development priorities will be developed. To inform the development of this framework, a non-systematic literature review has been carried out in order to understand the underlying causes of deforestation in Colombia, and how they can be linked to the food systems dimensions. This report presents the main findings of the literature reviewed.